The Contribution of the Nizamiyah Madrasah to the Development of Classical Islamic Education and Its Influence on the Modern World - Jumhana & Faridhah, Nurul Fajriah; Suria, Holisoh; Imas Nurazizah, Firmansyah (Mu'allim, 2026)
This study discusses the role of Madrasah Nizamiyah in the development of classical Islamic education and its influence on the modern education system. The purpose of this study is to reveal how Madrasah Nizamiyah, founded by Nizam al-Mulk during the Seljuk Dynasty, became a model of organized Islamic education and contributed greatly to the advancement of science. This research uses a qualitative method with a historical approach through a literature review of various primary and secondary sources. The results of the study show that Madrasah Nizamiyah not only played a role in strengthening the Ahlus Sunnah wal Jama'ah understanding and producing great scholars such as al-Ghazali, but also provided an educational system legacy that became the forerunner of modern higher education institutions. The concepts of boarding school education, scholarships, integrated curriculum, and government support in managing institutions have inspired the Islamic education system into the contemporary era